Ethylene dimethanesulfonate effects on gene promoter activities related to the endocrine function of immortalized Leydig cell lines R2C and MA-10 - de Barros, Jorge W.F. [UNESP]; Joule Pierre, Kenley; Kempinas, Wilma De G. [UNESP]; Tremblay, Jacques J. (Elsevier, 2024)
Ethylene dimethanesulfonate (EDS) is a molecule with known selective cytotoxicity on adult Leydig cells. A single intraperitoneal injection in rats but not mice, leads to male androgen deprivation and infertility. In vitro studies using rat and mouse immortalized Leydig cell lines, showed similar effects of cell death promoted by EDS in rat cells as seen in vivo, and suggest that EDS affects gene transcription, which could firstly compromise steroidogenesis before the apoptosis process. Using gene reporter assay, this study aimed to investigate EDS effects on the promoter activity of genes important for endocrine function (Star, Insl3) and response to toxic agents (Gsta3) in immortalized Leydig cell lines (rat R2C and mouse MA-10 cells), as well as identify possible EDS-responsive elements in the Star gene promoter. EDS exposure of R2C and MA-10 Leydig cells increased Gsta3 promoter activity after 4 h of treatment and decreased Insl3 promoter activity only in R2C cells after 24 h of treatment. EDS also decreased Star promoter activity in both Leydig cell lines. Using R2C cells, the EDS-responsive region in the Star promoter was located between −400 and −195 bp. This suggests that this region and the associated transcription factors, which include MEF2, might be targeted by EDS. Additional somatic gonadal cell lines expressing Star were used and EDS did not affect Star promoter activity in DC3 granulosa cells while Star promoter activity was increased in MSC-1 Sertoli cells after 24 h of treatment. This study contributes to the knowledge regarding the mechanism of EDS action in Leydig cells, and in other gonadal cell lineages, and brings new light regarding the rats and mice differential susceptibility to EDS effects, in addition to providing new avenues for experimental approaches to better understand Leydig cell function and dynamics in different rodent species.